Stress–strain relationships and yielding of metal-organic framework monoliths - Michele Tricarico; Cyril Besnard; Gianfelice Cinque; Alexander M. Korsunsky; Jin-Chong Tan (Communications Materials, 2023)
Abstract Metal-organic frameworks (MOFs) have emerged as a versatile material platform for a wide range of applications. However, the development of practical devices is constrained by their inherently low mechanical stability. The synthesis of MOFs in a monolithic morphology represents a viable way for the transition of these materials from laboratory research to real-world applications. For the design of MOF-based devices, the mechanical characterization of such materials cannot be overlooked. In this regard, stress-strain relationships represent the most valuable tool for assessing the mechanical response of materials. Here, we use flat punch nanoindentation, micropillar compression and Raman microspectroscopy to investigate the stress-strain behaviour of MOF monoliths. A pseudo-plastic flow is observed under indentation, where the confining pressure prevents unstable crack propagation. Material flow is accommodated by grain boundary sliding, with occasional stepwise cracking to accommodate excessive stress building up. Micropillar compression reveals a brittle failure of ZIF-8, while plastic flow is observed for MIL-68.